Health services across Europe face cuts as debt crisis begins to bite. (18th August 2011) - Houston, Muiris; Day, Michael; de Lago, Maria; Zarocostas, John
Abstract : As the eurozone debt crisis spreads to Italy and Spain, BMJ correspondents investigate its effects on health services in four of the hardest hit countries